2018
DOI: 10.1111/rge.12193
|View full text |Cite
|
Sign up to set email alerts
|

Geological and Geochemical Characteristics of Gold Mineralization in the Salu Bulo Prospect, Sulawesi, Indonesia

Abstract: The Salu Bulo prospect is one of the gold prospects in the Awak Mas project in the central part of the western province, Sulawesi, Indonesia. The gold mineralization is hosted by the meta-sedimentary rocks intercalated with the meta-volcanic and volcaniclastic rocks of the Latimojong Metamorphic Complex. The ores are approximately three meters thick, consisting of veins, stockwork, and breccias. The veins can be classified into three stages, namely, early, main, and late stages, and gold mineralization is rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Aside from these relatively young rocks in the magmatic arc, the Cretaceous accretionary complexes also have potential for gold mineralization, as indicated by recent discoveries of gold prospects and deposits in eastern Indonesia (e.g., Idrus et al, 2017). Discoveries of gold mineralization hosted in the Cretaceous metamorphic terrains such as the Awak Mas gold deposits in South Sulawesi (Ernowo et al, 2019; Hakim et al, 2018; Tuakia et al, 2018), the Bulu gold prospect in Maluku, and the Bombana gold prospect in Southeast Sulawesi (Idrus et al, 2017) have shown that the metamorphic terrains represent an alternative for gold exploration in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from these relatively young rocks in the magmatic arc, the Cretaceous accretionary complexes also have potential for gold mineralization, as indicated by recent discoveries of gold prospects and deposits in eastern Indonesia (e.g., Idrus et al, 2017). Discoveries of gold mineralization hosted in the Cretaceous metamorphic terrains such as the Awak Mas gold deposits in South Sulawesi (Ernowo et al, 2019; Hakim et al, 2018; Tuakia et al, 2018), the Bulu gold prospect in Maluku, and the Bombana gold prospect in Southeast Sulawesi (Idrus et al, 2017) have shown that the metamorphic terrains represent an alternative for gold exploration in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…The Awak Mas gold deposit is situated in the southern arm of the Western Sulawesi Province, where both metamorphic basement units and arc-related igneous units prevail (Figure 1b). The Latimojong Formation is underlaid by phyllites, slates, basic to intermediate volcanics, limestones, and schists, representing a platform and/or fore arc trough flysch sequence intruded by granite, diorite, monzonite, and/or syenite plugs and stocks [16][17][18][19][20][21][22]. The other lithological formation in this area is the Lamasi Complex, composed of mafic to intermediate rocks.…”
Section: Introductionmentioning
confidence: 99%